Penggunaan Metode SPC (Statistical Process Control) pada Proses Pengendalian Kualitas Produk DC di PT. X - Baidawih, Muhammad Hafidz; Nugraha, Asep Erik (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
X is a company that operates in the cigarette production sector. This company has 4 sections for the production process, namely printing (offset), cutting (auto platten), folding (folder), and packaging (packing). Of the four sections, the one most at risk of experiencing machine downtime is the folding section, because this section is where the production process of all products passes. DC products are one of the products from PT. X which is widely used by consumers, the number of product defects DC. The aim of this research is to identify the types of defects that often occur, and identify the main causes of defects that occur in DC products using the SPC method. Types of defects found Inappropriate color, Dents on the product, and not folded on the product. Of the three types of defects that exist, the most dominant type of defect is dents on products with a total of 12,595 pcs, followed by products that are not folded with a total of 9,142 pcs, and finally the color does not match with a total of 8,651 pcs. Keywords: Defect Product, Quality Control, Statistical Process Control